Development of Android Learning Media to Improve Students' Mathematical Communication Skills on Social Arithmetic Material - Sya'diyah, Zahrotusy; Arifin (International Journal of Research in Mathematics Education, 2024)
Mathematical communication skills are students’ ability to convey mathematical ideas or ideas which can be done orally or in writing as well as the ability to understand or accept other people's mathematical ideas. Learning at MTs Negeri 2 Purbalingga students still have a low level of mathematical communication skills, because learning still uses conventional learning media and does not involve students. The choice of learning media is an important thing to pay attention to and apply. The development of science and technology is increasingly advanced, so the learning media developed must also be more innovative, especially if it involves the role of technology in it. Therefore, the aim of this research is to develop valid and effective android based interactive learning media to improve students’ mathematical communication skills in class VII social arithmetic material at MTs Negeri 2 Purbalingga. The research method used in this research is Research and Development (R&D). The results of this study indicate that the android based learning media is declared valid and suitable for use with percentage results in the validation of material expert by 91.66%, media experts by 93.3%, teacher assessment by 92.5%, small group test assessment by 88.81%, and the field test assessment is 92,68%. Furthermore, the android based learning media developed is effective in improving students' mathematical communication skills with the t-test results getting a significance of 0.000 where the results are smaller than the significance limit of 0.05, so it can be concluded that H0 is rejected and H1 is accepted.